Method for predicting the risk of type 2 diabetes mellitus development in persons with visceral obesity and prediabetes - Yulia V. Nelaeva; Alsu A. Nelaeva; Anna E. Yuzhakova; Ivan M. Petrov; Igor F. Sholomov (Терапевтический архив)
Aim. To create a mathematical model, which will predict the development of type 2 diabetes mellitus (DM 2) in individuals with visceral obesity and/or prediabetes.